Phenethyl isothiocyanate suppresses the benzo[a]pyrenemediated rise in hepatic CYP1A1 mRNA - Konsue, Nattaya; Abdull Razis, Ahmad Faizal (2014)
Phenethyl isothiocyanate (PEITC), the most comprehensively studied aromatic isothiocyanate, has been shown to act as anticancer agents mainly through inducing phase II enzymes responsible for metabolising carcinogens in the body. Humans are often exposed to carcinogenic factors, some of which are through the diet. Polycyclic aromatic hydrocarbons are commonly and abundantly found in the environment, particularly via the consumption of over-cooked meats. One of the most abundant polycyclic aromatic hydrocarbons is benzo[a]pyrene. Phase II enzymes are responsible for the detoxification of this carcinogen in the body. In spite positive effects of this isothiocyanate on phase II enzymes, its effect on the phase I bioactivating enzyme cytochrome P450 1a1 (CYP1A1) is still unclear. Therefore, the overall objective of this study was to investigate the effect of PEITC on the benzo[a]pyrene-mediated rise in hepatic CYP1A1 mRNA. Precision cut-rat liver slices were exposed to benzo[a]pyrene at 1 and 5 μM in the presence of PEITC (1-25 μM) for 24 hours and CYP1A1 mRNA levels were determined using quantitative polymerase chain reaction (QPCR). Our findings revealed that PEITC suppressed benzo[a]pyrene-mediated rise in hepatic CYP1A1 mRNA in a dose-dependent manner. It is demonstrated that PEITC can directly inhibit bioactivation of polycyclic aromatic hydrocarbon benzo[a]pyrene, indicating its chemopreventive potential.